Evolusi Nama-Nama Tuhan dalam Islam: (Perspektif Tafsir Kronologis Muhammad Abid Al-Jabiri) - Umi Wasilah; Zaimuddin Zaimuddin (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
The discourse on the study of the evolution of the names of God in Islam with the perspective of Muhammad Abid al-Jabiri's chronological interpretation, has an emphasis on the realm of the revelation of the Qur'an. The purpose of this study is to find out, examine, and reveal the evolution of the names of God as outlined by al-Jabiri in his chronological interpretation. This research was assisted by qualitative research with library research methods, accompanied by documentation as data collection. While the data analysis is in the form of descriptive-analysis with research theory taken from the perspective of Hans Georg Gadamer. The result of this study is an understanding that the name of God appears from the identifiers of the names Rab, Allah, and Ar-Rahman, which is then followed by the introduction of al-asma’ al-husna afterwards. In al-Jabiri's perspective the use of the word Rab is related to prophethood (nubuwwah) and divinity (rububiyah). Furthermore, regarding the mention of God's name with the word Allah, it is related to the problem of worshiping Allah (uluhiyyah). Lastly, ar-Rahman lafadz in the mention of Allah was born from the revelation of Surah al-Fatihah. The existence of this ar-Rahman lafadz later became the beginning of the birth of the names al-asma’ al-husna as the mention of the names of Allah.